PENERAPAN RESTORATIVE JUSTICE TERHADAP PELAKU TINDAK PIDANA PEMBAKARAN HUTAN DI WILAYAH HUKUM KABUPATEN PELALAWAN - Robet Chandro Wijaya Sibuea; Zulfikar Jayakusuma; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Forest is an ecosystem unit in the form of a large expanse of landcontaining biological natural resources which are dominated by trees in theirnatural environment which cannot be separated from one another. Forest andland fires are natural disasters that often occur in Indonesia, especially duringthe dry season. These fires cause enormous environmental damage, economiclosses, and social problems. In fact, large forest and land fires result indevastating haze impacts beyond state administrative boundaries (transnationaldisasters). The regulation of lightly motivated criminal acts is a crime regulatedin the Criminal Code (KUHP) as well as in other laws and regulations, but thedifference must be seen from the background of the perpetrator, the motives andconsequences of the crime not to cause disturbing losses. in society, but thepractice of law enforcement disturbs the sense of justice a lot, because it isresolved through a court trial process which is actually not necessary or can bepursued by a process outside the court, by prioritizing peace by deliberation toreach consensus is an integral mechanism in people's lives in Indonesia, namelythe Restorative Justice path. Law enforcement against forest fires in PelalawanRegency, Riau Province based on Law Number 41 of 1999 concerning Forestryhas not been implemented as expected. Although everyone is prohibited fromburning forests, it turns out that every year forest fires routinely occur inPelalawan Regency, but there are still many land arsonists who do not get justicein the punishment they get. The type of research used by the author is sociologicallegal research, namely research that examines the legal aspect by looking at theapplicable legislation and comparing it with its implementation in the field bymeans of a survey.Keywords: Justice, Restorative justice, Forest Fire